The identification of drug related problems (DRPs) using profilaxis antibiotics in orthopedic surgical patients at a Government Hospital in Yogyakarta - Happy Elda Murdiana (Universitas Islam Indonesia, 2021)
Background: Antibiotic prophylaxis in orthopedic surgery cases aims to prevent surgery site infections (SSI). For antibiotic prophylaxis, it is recommended to use the first generation of cephalosporin, namely cefazolin which can kill the bacteria commonly found in orthopedic surgery infection. The prophylactic administrationof cefotaxime is not the first line but is definitive for surgical prophylaxis.Objective: The aim of this study was to determine the rationale for the use of antibiotic prophylaxis for orthopedic surgery, the drug problems (DRPs) that occurred and their potential interactions.Method: This study was conducted using a cross sectional design with a total sampling technique of medical record samples from January to February 2019 at the Government Hospital in Yogyakarta. Observational analytical descriptive data processing by ensuring the appropriate of indications, route of administration,timing of administration and an appropriate of prophylactic doses as well as how to compare DPRs to the literature and analysis of potential co drug interaction with Drug Information Handbook (DIH), AHFS Clinical Drug Information, Drug Interaction Facts, and Interactions Stockley’s Drug Interaction.Results: All patients received appropriate therapy for indication, type of drug, routes of administration for pre and postoperative. All patients received an under dose of ranitidine and 1 patient (1,69%) received an over dose of piracetam. Potential interactions that occur include ketorolac-ranitidine, NSAIDs with other NSAIDs, NSAIDs-ranitidine, NSAIDs-ACEi, NSAIDs-bisoprolol, bisoprolol-calcium, calcium-vitamin C, and paracetamol-ranitidine.Conclusion: Pre and postoperative prophylactic antibiotics are rational. The accompanying drug, ranitidine and piracetam were not properly doses. Drug interactions in this study are potential.Keywords: prophylaxis antibiotic, orthopedic surgery, cefotaxim, DRPs IntisariLatar belakang: Profilaksis antibiotic pada kasus bedah ortopedi bertujuan mencegah timbulnya Infeksi Luka Operasi (ILO). Profilaksis antibiotik untuk bedah disarankan menggunakan sefalosporin generasi pertama yaitu cefazolin yang dapat membunuh bakteri s. aureus yang biasa terdapat pada infeksi bedah ortopedi. Pemberian profilaksis cefotaxim bukan lini pertama tetapi direkomendasikan untuk profilaksis bedah.Tujuan: Penelitian ini bertujuan mengetahui kerasionalan (DRPs) penggunaan antibiotik profilaksis bedah ortopedi dan obat penyerta yang diberikan.Metode: Penelitian ini menggunakan metode rancangan cross sectional, teknik total sampel dilakukan dalam pengambilan sampel rekam medis bulan Januari–Februari 2019 di Rumah Sakit Pemerintah di Yogyakarta. Pengolahan data deskriptif analitik observasional dengan menganalisa ketepatan indikasi, jenis obat, rute pemberian, waktu pemberian dan ketepatan dosis antibiotic profilaksis serta obat penyerta dengan cara membandingkan DRPs terhadap literatur dan menganalisa potensi interaksi obat penyerta dengan buku Drug Information Handbook (DIH), AHFS Clinical Drug Informaton, Interaction Drug Fact, dan Stockley’s Drug Interaction.Hasil: Semua pasien mendapatkan terapi tepat indikasi, jenis obat, rute pemberian, dan tepat dosis pemberian obat untuk pre dan paska pembedahan. Semua pasien menerima dosis kurang untuk terapi penyerta ranitidin dan 1 pasien (1,69%) menerima piracetam dosis berlebih. Potensial interaksi yang terjadimeliputi ketorolak-ranitidin, NSAID dengan NSAID lain, NSAID-ranitidin, NSADI ACEI, NSAID-bisoprolol, bisoprolol-kalsium, kalsium-vitamin C, dan paracetamol-ranitidinKesimpulan: Pemberian antibiotik profilaksis pra dan paska pembedahan rasional. Obat penyerta berupa ranitidin dan piracetam tidak tepat dosis. Interaksi obat pada penelitian ini bersifat potensial.Kata kunci: antibiotik profilaksis, bedah ortopedi, cefotaxim, DRPs